Association of the angiotensinogen M235T polymorphism with recurrence after catheter ablation of acquired atrial fibrillation. (December 2015) - Wang, Qunshan; Hu, Xiaofeng; Li, Shuyuan; Wang, Xiaofeng; Wang, Jun; Zhang, Rui; Sun, Jian; Zhang, Pengpai; Feng, Xiangfei; Li, Yi-Gang
Purpose: Previous studies showed that genetic variants of the angiotensinogen ( AGT ) gene conferred higher risk for acquired atrial fibrillation (AF). The present study investigated whether AGT variants correlate with the clinical outcome in patients with acquired AF after catheter ablation (CA). Methods: A total of 150 acquired symptomatic drug-refractory AF patients (mean age 63.7±11.0 years, 24.6% non-paroxysmal AF) with acquired AF underwent a single CA procedure in our department and were included in this retrospective analysis. Eight tagging single nucleotide polymorphisms (tSNPs) in the AGT gene were genotyped. Standard electrocardiographs (ECGs) and 24-hour Holter recordings were performed during a median follow-up period of 57.5 months to detect AF recurrence. Results: Sixty-one patients (40.7%) suffered AF recurrences after a single CA procedure during follow up. Of the eight tSNPs, the frequency of the M allele of M235T was significantly higher in the recurrence group (28%) compared to the non-recurrence group (18%) ( p =0.042). The recurrence rates of patients with the TT, MT, and MM genotypes were 34.4%, 50%, and 55.6%, respectively ( p trend =0.049). After adjusting for age, sex, body mass index, hypertension, left atrial volume index (LAVI) and other covariates, M235T increased the risk of AF recurrence in additive and dominant models with odds ratios of 2.023 (95% confidence interval (CI): 1.034–3.926, p =0.033) and 2.601 (95% CI: 1.102–6.056, p =0.025), respectively. However, in multiple correction analyses, the p values of multiple comparisons were not statistically significant ( p correct >0.05). Conclusions: The M allele of M235T might be associated with an increased risk of AF recurrence after CA. Genotyping may thus be helpful on identifying patients with higher risks of AF recurrence after CA and developing optimal follow-up strategies. These strategies may differ and should be individualized according to patients' genotype. Future studies are warranted to validate the potential effect of AGT M235T on AF recurrence post CA.